A study on the factors influencing employee's motivation in Petronas Penapisan (Melaka) Sdn Bhd / Muhammad 'Izzat Ishak and Muhammad Afiq Ahlami Azman - Ishak, Muhammad 'Izzat; Azman, Muhammad Afiq Ahlami (Faculty of Business and Management, Universiti Teknologi MARA, 2014)
The study aims to identify the factors influencing employee's motivation in PETRONAS Penapisan (Melaka) Sdn Bhd. It is very important for an organization to ensure that the employees are highly motivated. In this research, the researchers chooses four factors which are employee involvement, reward and recognition, job security and organizational culture. 100 respondents were chosen from the total population from five departments in the organization by using simple random sampling. These five departments are Human Resource Management and Administration, Finance, Legal and Corporate Affairs, Engineering and Health Safety Environment and Security department. The findings of the study are, all independent variables have significant relationship with employee's motivation. The researchers also found that employee involvement is the most significant predictor variable. Overall, the researchers able to answer all objectives.